Analysis Of The Accounting Information System For Cash Receipts And Disbursements At PT Pos Indonesia (Persero) Gunungsitoli Branch - Zebua, Jul Alvandi Samolala; Zai, Kurniawan Sarototonafo; Zebua, Dedi Irawan; Waruwu, Noviza Asni (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the accounting information system used in the process of cash receipts and disbursements at PT Pos Indonesia (Persero) Gunungsitoli Branch Office. The accounting information system functions as a tool to record, manage, and convey financial information systematically in order to support the smooth operation of the company. In practice, the company has implemented a Standard Operating Procedure (SOP) as a guideline for financial activities. However, it has not yet been supported by a flowchart, which plays an important role in visually describing the process flow and facilitating task comprehension and execution. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the cash receipt system is carried out through several service units such as Oranger Counter, Oranger Mobile, Post Agents, and Sub-Branch Offices, with recordings based on the Point of Sales (POS) system. Cash disbursements are made for essential operational needs and are submitted through a fund request form by each division, approved by the branch head, and processed through the Entry Pra-NPP system by the head office. Based on these findings, it can be concluded that the implemented accounting information system has not fully met the criteria of an ideal system. This is due to the absence of a visualized workflow in the form of a flowchart that could clarify work procedures, accelerate understanding, and reduce the potential for procedural errors. Therefore, the preparation and implementation of a flowchart are strongly recommended as a complement to the existing SOP.